The Impact of Using Modern Information and Communication Equipment and Services on Driving Safety - Jovović, Ivan; Peraković, Dragan; Husnjak, Siniša (Promet - Traffic&Transportation, 2018)
With the development and application of modern information and communication equipment and services (ICES), global society has undergone significant development and progress in everyday life. Along with the positive, negative aspects of their usage have evolved. One of the problems is the new sources of driver distraction, which ultimately results in a serious, growing daily threat to traffic safety. Simultaneously with the development of ICES, the number of distracters (mobile terminal devices, laptops, smart watches, and others) has increased as well, which also reduces the level of safety and affects the quality of driving. With the increase in participation and ownership of mobile terminal devices, as well as the implementation of modern multimedia information and communication systems in vehicles, this problem will further escalate in the coming years. The unfavorable factor comes from the fact that distraction factors influenced by using ICES belong to bio-mechanical, cognitive, auditory, and visual categories, which directly affects essential human functions for successful and safe vehicle operation. This paper provides insight into the issue of distraction factors that affect drivers with an emphasis on those caused by using modern ICES.